2019
DOI: 10.1186/s13046-019-1067-5
|View full text |Cite
|
Sign up to set email alerts
|

SHMT1 inhibits the metastasis of HCC by repressing NOX1-mediated ROS production

Abstract: BackgroundHepatocellular carcinoma (HCC) is the most major type of primary hepatic cancer. Serine hydroxymethyltransferase 1 (SHMT1) is recently found to play critical roles in human cancers including lung cancer, ovarian cancer and intestinal cancer. However, the expression, function and the underlying mechanisms of SHMT1 in HCC remain uncovered.MethodsqRT-PCR, immunohistochemistry and immunoblotting were performed to detect the expression of SHMT1 in HCC tissues and cell lines. HCC cell migration and invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 42 publications
0
39
0
Order By: Relevance
“…RNA extraction and qRT-PCR were performed as previously described 18 . 18S RNA was used as an internal control.…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…RNA extraction and qRT-PCR were performed as previously described 18 . 18S RNA was used as an internal control.…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…Immunohistochemistry (IHC) staining was performed as described previously 18 . The following antibodies were used in the IHC staining: BRD9 antibody (1:50) and TUFT1 antibody (1:50).…”
Section: Immunohistochemistry (Ihc) Stainingmentioning
confidence: 99%
“…Four-week BALB/c nude mice were purchased from Shanghai SLAC Laboratory Animal Company (Shanghai, China). The in vivo tumor growth and lung metastasis experiments were performed using Hep3B cells with or without USP13 knockdown according to the protocols as previously described (Dou et al, 2019a;Guo et al, 2019). The tumor volume (V) was calculated as follows: V = (L × D2)/2 where L and D represent the tumor length and width, respectively (in mm).…”
Section: In Vivo Experimentsmentioning
confidence: 99%
“…In addition, when activated, liver resident Kupffer cells (KCs) release an 'oxidative burst' of superoxide and numerous other products with cytotoxic, pro-in ammatory and growthpromoting activity, and attract circulating immune cells to the liver; all contributing to the establishment of a tumor-promoting microenvironment. ROS also contribute to cancer development and progression, by acting as second messengers in disease-driven intracellular signaling pathways controlling cell proliferation, survival, motility and invasiveness, as well as by controlling the reactivity of stromal components that are fundamental for cancer development and dissemination, in ammation, tissue repair, and de novo angiogenesis (11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on human HCC samples showed that high NOX1 levels are correlated with a poor prognosis (24,25). The involvement of NOX1 in cell proliferation, tumor growth, cell motility, epithelial-mesenchymal transition (EMT) and matrix metalloproteinase-2 production has been shown in in vitro studies (13,14). NOX1-/-knockout mice and mice with myeloid NOX1 disruption were reported to develop fewer and smaller tumors following diethylnitrosamine (DEN) injection.…”
Section: Introductionmentioning
confidence: 99%